The Bloch space and the dual space of a Luecking-type subspace of. Issue 10 (3rd October 2018) - Bao, Guanlong; Ye, Fangqin
Abstract: Let X be the dual space of a Luecking-type subspace of the Bergman spaceA 1 . It is known that the Bloch spaceB is a subset of X . In 1990, Ghatage and Sun asked whetherB is dense in X . They also asked whether the little version of X is a subset ofB . In this note, based on results and methods of Girela, Peláez, Pérez-González and Rättyä in 2008, we answer the two questions in the negative.